Utilization of Cocoa Pod Husk Waste as Fuel for Downdraft Type Gasification Reactor of a Capacity of 960 Liters in Berau Regency - Tidar, Feri Putra Prakus; Fajri, Renal (STMIK Widya Cipta Dharma, 2024)
This experiment aims to investigate the performance characteristics of a downdraft gasification reactor fueled by cocoa pod husk as a technological solution for obtaining alternative renewable energy sources to replace fossil fuels and natural gas. The research was conducted experimentally on a gasification reactor made of SS310 thermal-resistant carbon steel material. The reactor has dimensions of 35 centimeters in diameter and 250 centimeters in height. Measurements in the gasification zone were performed using seven K-type thermocouples installed along the reactor wall. Fuel was fed continuously at a rate of 4 kg/hour. The research involved varying the temperature in the oxidation zone at 900 ºC, 950 ºC, 1000 ºC, 1050 ºC, and 1100 ºC. Data collection was carried out at these different temperature variations and processed to determine the performance parameters of the gasification reactor, including gas composition, temperature distribution along the reactor wall, and the lower heating value (LHV) of the syngas produced. The results showed the highest temperature distribution in the drying zone (205 ºC), pyrolysis zone (575 ºC), and reduction zone (520 ºC), obtained at an oxidation temperature of 1100 ºC. Meanwhile, the optimum syngas quality was achieved at an oxidation temperature of 1000 ºC, with the composition of flammable syngas CO, H₂, and CH₄ being 27.08%, 8.53%, and 2.41%, respectively, and the highest LHV of 5206 kJ/m³. In general, increasing the oxidation temperature contributed positively to the performance of the gasification reactor using cocoa pod husk waste.